HISTORICAL DEVELOPMENT OF AMERICAN PROSE AS A LITERARY TREND - Og‘abek Yuldashev Komiljon o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
In the following article is about Historical development of American prose as as literary trend. It is devoted to the study of of American prose as as literary trend. This theme is chosen for because of its importance for learning English language. In the process of learning English the learning of the literature of exact country is very important. Alongside with English literature we must know American literature, which developed on the basis of English one.